New generic assignment to the harvestman Metaphareus punctatus (Opiliones: Stygnidae) and observations about it reproductive behavior - Osvaldo Villarreal M.; Nestor Sánchez; Antonio De Ascenção (Iheringia: Série Zoologia, 2019)
ABSTRACT We herein propose the transfer of Metaphareus punctatus Roewer, 1913, to the genus Eutimesius Roewer, 1913 (Heterostygninae) based on the genital morphology of the species and morphology of tarsi III and IV, resulting in the new combination Eutimesius punctatus (Roewer, 1913), comb. nov. New geographical records for E. albicinctus (Roewer, 1915) are offered, recording sympatry between the congeneric species E. albicinctus and E. punctatus and data on the reproductive behavior of E. punctatus are presented, suggesting the existence of parental care in this species.